A miniaturized ultra‐wideband planar monopole antenna with L‐shaped ground plane stubs. Issue 11 (20th August 2019) - Tan, Ming‐Tao; Li, Jian‐Qi; Jiang, Zhi‐Yong
Abstract: This article presents a miniaturized ultra‐wideband planar monopole antenna with an oval radiator. The proposed antenna is fed by a coplanar waveguide (CPW), and two L‐shaped stubs are extended from the ground plane of the CPW. This presented antenna is able to produce resonances in the lower frequency band and realize better impedance matching performance in the middle and higher frequency bands with the aid of the L‐shaped stubs. The antenna was built and tested. The total size of the proposed antenna is only 26 × 20 × 1.6 mm 3 . Its measured –10 dB impedance bandwidth is 10.1 GHz (3.1‐13.2 GHz). The measured far‐field radiation patterns are stable in the whole operating frequency band.